Minimally invasive surgery for pediatric renal and ureteric stones: A therapeutic update - Peng, Tao; Zhong, Hongcai; Hu, Baohui; Zhao, Shankun (Frontiers in Pediatrics, 2022)
The incidence of pediatric urolithiasis (PU) is growing worldwide. The corresponding therapeutic methods have become a research hot spot in pediatric urology. PU has the characteristics of abnormal metabolism, easy recurrence, and immature urinary system development, which make its treatment different from that of adults. Pediatric urologists should select the optimal treatment modality to completely remove the stones to prevent recurrence. Currently, the curative treatments of PU include extracorporeal shock wave lithotripsy (ESWL), ureteroscopy, retrograde intrarenal surgery, percutaneous nephrolithotomy (PCNL), laparoscopic, robot-assisted laparoscopic, and open surgery. This review aims to conduct a therapeutic update on the surgical interventions of both pediatric renal and ureteric stones. It accentuates that pediatric surgeons or urologists should bear in mind the pros and cons of various minimally invasive surgical treatments under different conditions. In the future, the treatment of PU will be more refined due to the advancement of technology and the development of surgical instruments. However, a comprehensive understanding of the affected factors should be taken into account by pediatric urologists to select the most beneficial treatment plan for individual children to achieve precise treatment.